(untitled) (Fiep Bulletin - online, 2011)
Essential the Arterial Hypertension is an illness chronic, multifactorial, and characterized for the raised tensional levels, considered one of the main factors of risk of cardiovascular morbidity and mortality. The treatment of the PA by means of the programmed physical exercises (endurance and resisted) has been recommended. Some studies had verified that the physical training contributes positively in the reduction of the arterial pressure of hypertension individuals. The hydro gymnastics as carried through physical exercise in half liquid, in accordance with makes possible the objective, modifications in flexibility, muscular force and located muscular resistance in programs of physical conditioning. The competing training is the association of the training of endurance with the resisted training inside of a program of physical conditioning, and this combination can occur inside of alternating form of a session, or in alternating days of training. Study of case with composed sample for two adult women hypertension (period of training 1), public officers and voluntary in the study. The research had duration of five months, where the volunteers had initially presented the laboratorial professors, examinations and later, the tests of physical evaluation had been submitted. Before the beginning of the training in water, the clinical examinations had been evaluated by a doctor, who followed the process. Considering the profile of the volunteers, the results can have been influenced for external, ambient factors, motivation, age, sex and everything that if can correlate with the final result. The verified positive alterations demonstrate that the TC was efficient in the tested 0 variable, mainly when associates with the improvement of the health and quality of life. In this in case that, the TC in water can have positively contributed for reduction of corporal weight, the reduction of the taxes of cholesterol-t, TG, LDL, and the increase of the HDL. Finally, the physical exercise promoted quality of life and health of the volunteers.